Implementing Digital Educational Resources: a Systematic Review From a Differential Calculus Teaching Perspective: Implementación de recursos educativos digitales, una revisión sistemática desde la enseñanza del Cálculo Diferencial - Mora Casasola, María Fernanda (2023)
The use of digital educational resources in the teaching and learning process of Differential Calculus is increasingly frequent. This implementation is an alternative for the construction of meaningful learning of various topics, as well as for the reduction of high dropout rates. This analysis consists of a systematic review to know what digital educational resources have been used in the past five years in differential calculus and the justification for such use. For the study, three repositories were consulted, in which thirty articles in total were selected. The results include the growing systematization of experiences related to this topic, and the importance of incorporating these resources as a way to break with the traditional paradigms that prevail in the teaching of calculus. Based on the review, it is generally important for educational institutions to acquire appropriate equipment for both teachers and students, to promote teacher training in the use of these resources, and to make implementation appropriate to the students’ learning needs.